Revisiting the mechanism of redox-polymerization to build the hydrogel with excellent properties using a novel initiator. Issue 9 (1st February 2016) - Zhang, Sai; Shi, Zixing; Xu, Hongjie; Ma, Xiaodong; Yin, Jie; Tian, Ming
Abstract : We propose a novel and facile approach to prepare excellent hydrogels by using PEA as initiating and crosslinking centers. Abstract : In this paper, polyetheramine, a kind of linear epoxy polymer, has been used as both an initiator and a cross-linker for the synthesis of polyacrylamide hydrogel by means of a one pot method, which is a simple, time saving, facile and easily controlled process and the obtained hydrogel showed super stretchable and highly elastic properties. More impressively, only very low content of polyetheramine (0.1 wt%) could exhibit greatly enhanced mechanical properties toward polyacrylamide and the properties of hydrogel could be easily tailored by the weight ratio of polyetheramine to acrylamide. These hydrogels could be stretched up to 2000% with a maximal fracture energy up to 3.2 MJ m −3 . These types of hydrogels could be recovered immediately with low residual strains upon unloading even after 1000% strain. The presence of polyetheramine could create a more homogeneous distribution of crosslinking points and can dissipate the energy effectively, which can be responsible for the improved mechanical properties.